Inhibition of Endothelial–Mesenchymal Transition Mediated by Activin Receptor Type IIA Attenuates Valvular Injury Induced by Group A Streptococcus in Lewis Rats - Zirong Lu; Yuan Li; Chuanghong Lu; Zhongyuan Meng; Ling Bai; Feng Huang; Zhiyu Zeng (Frontiers in Bioscience-Landmark)
Background: Rheumatic heart disease (RHD), which is caused mainly by Group A Streptococcus, leads to fibrotic damage to heart valves. Recently, endothelial‒mesenchymal transition (EndMT), in which activin plays an important role, has been shown to be an important factor in RHD valvular injury. However, the mechanism of activin activity and EndMT in RHD valvular injury is not clear. Methods: Our study was divided into two parts: in vivo and in vitro. We constructed a small interfering RNA (ACVR2A-siRNA) by silencing activin receptor type IIA (ACVR2A) and an adeno-associated virus (AAV-ACVR2A) containing a sequence that silenced ACVR2A. The EndMT cell model was established via human umbilical vein endothelial cells (HUVECs), and the RHD animal model was established via female Lewis rats. ACVR2A-siRNA and AAV-ACVR2A were used in the above experiments. Results: EndMT occurred in the valvular tissues of RHD rats, and activin and its associated intranuclear transcription factors were also activated during this process, with inflammatory infiltration and fibrotic damage also occurring in the valvular tissues. After inhibition of ACVR2A, EndMT in valvular tissues was also inhibited, and inflammatory infiltration and fibrosis were reduced. Endothelial cell experiments suggested that mesenchymal transition could be stimulated by activin and that inhibition of ACVR2A attenuated mesenchymal transition. Conclusions: Activin plays an important role in signal transduction during EndMT after activation, and inhibition of ACVR2A may attenuate RHD valvular damage by mediating EndMT. Targeting ACVR2A may be a therapeutic strategy to alleviate RHD valvular injury.